PENGARUH PERTUMBUHAN EKONOMI, JUMLAH ANGKATAN KERJA, DAN INFLASI TERHADAP TINGKAT PENGANGGURAN DI PROVINSI JAWA TIMUR (2007-2016) - ANSHORI, ZULKIFLI; SUPARTA, I MADE (JEB17 : Jurnal Ekonomi dan Bisnis, 2018)
ABSTRACTThe problem of unemployment is a common problem experienced by various countries and regions even though it triggers social problems including criminal acts in the economy. This situation can reduce people's living standards. If the low unemployment rate means that the standard of living of the people increases and encourages the economy to grow. The solution to overcoming the problem of unemployment focuses not only on a small portion (micro) but also mostly / entirely (macro). Decisions that must be focused include rising prices / inflation, human resources and triggering a growing economy. The following research analyzes the magnitude of the influence of economic growth, the number of labor force, and inflation on unemployment in East Java. Analysis with the aim of knowing how the variables of economic growth, the number of labor force, inflation affect the unemployment rate variable in East Java so that later it can be used as one of the basis for determining decisions in reducing unemployment in East Java. The data used in this study are secondary data obtained from the Central Statistics Agency (BPS) and browsing internet websites as supporters. In this analysis using the method of multiple linear regression analysis that produces how much influence the economic growth, the number of labor force, and inflation on the unemployment rate in East Java. From the results of this study using a multiple linear regression analysis method obtained an alternative hypothesis (Ha) that is there is no significant effect of economic growth on unemployment in East Java, there is a significant effect on the number of unemployed labor force in East Java, and there is a significant effect of unemployment inflation in East Java.